1990
DOI: 10.1002/cjce.5450680305
|View full text |Cite
|
Sign up to set email alerts
|

Performance of combined mesh packing and sieve tray in distillation

Abstract: The hydraulic and mass transfer performance of a combined knitted mesh packing and sieve tray has been measured for the distillation of methanol-water mixtures. It was found that by adding a shallow bed of packing, the Murphree tray efficiency increased by 40-50% over a wide range of concentrations and flow rates. This increase in tray efficiency can be attributed to a much smaller and more uniform bubble formation on the packed tray. Hydraulic measurements have shown that the packed trays have lower weeping a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The distillation experiments were carried out at total reflux under ambient pressure in a 0.153 m diameter column. Schematic diagrams of the experimental apparatus and a complete description of the facilities as well as operational procedures were given previously (Chen et al, 1990). The dimensions of the column and test trays are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The distillation experiments were carried out at total reflux under ambient pressure in a 0.153 m diameter column. Schematic diagrams of the experimental apparatus and a complete description of the facilities as well as operational procedures were given previously (Chen et al, 1990). The dimensions of the column and test trays are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have been made to better understand tray efficiency, pressure drop, capacity, weeping an entrainment rates. A previous study has shown that a bed of mesh packing on sieve trays can increase the tray efficiency (Chen et al, 1990). However, foulig may occur on the mesh packing, which in turn may reduce the tray lifetime.…”
Section: Introductionmentioning
confidence: 98%